Interhemispheric sleep EEG asymmetry in the rat is enhanced by sleep deprivation. - Vyazovskiy, V; Borbély, A; Tobler, I (2002)
Vigilance state-related topographic variations of electroencephalographic (EEG) activity have been reported in humans and animals. To investigate their possible functional significance, the cortical EEG of the rat was recorded from frontal and parietal derivations in both hemispheres. Records were obtained for a 24-h baseline day, 6-h sleep deprivation (SD), and subsequent 18-h recovery. During the baseline 12-h light period, the main sleep period of the rat, low-frequency (<7.0 Hz) power in the non-rapid eye-movement (NREM) sleep EEG declined progressively. Left-hemispheric predominance of low-frequency power at the parietal derivations was observed at the beginning of the light period when sleep pressure is high due to preceding spontaneous waking. The left-hemispheric dominance changed to a right-hemispheric dominance in the course of the 12-h rest-phase when sleep pressure dissipated. During recovery from SD, both low-frequency power and parietal left-hemispheric predominance were enhanced. The increase in low-frequency power in NREM sleep observed after SD at the frontal site was larger than at the parietal site. However, frontally no interhemispheric differences were present. In REM sleep, power in the theta band (5.25-8.0 Hz) exhibited a right-hemispheric predominance. In contrast to NREM sleep, the hemispheric asymmetry showed no trend during baseline and was not affected by SD. Use-dependent local changes may underlie the regional differences in the low-frequency NREM sleep EEG within and between hemispheres. The different interhemispheric asymmetries in NREM and REM sleep suggest that the two sleep states may subserve different functions in the brain.